Majaz and Kinayah in the Psychological Dialogue of Surah Yusuf - Najwa Nadia, (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study examines the rhetorical dimensions in the dialogues of Surah Yusuf, which represent the emotional dynamics of its characters through implicitly meaningful expressions. The aim of this research is to analyze the forms and functions of majaz and kinayah as part of the study of ‘ilm al-bayan in framing the psychological narrative of the Qur’an. The method employed is a qualitative approach with textual analysis of selected verses containing these two rhetorical devices. The data are analyzed contextually to uncover the underlying rhetorical meanings. The results of the study indicate that the use of majaz and kinayah in Surah Yusuf functions not only as elements of linguistic aesthetics but also plays a significant role in refining the delivery of messages, strengthening the psychological expressions of the characters, and deepening the emotional dimension of the storyline. These findings demonstrate that the rhetorical beauty of the Qur’an, as studied within ‘ilm al-bayan, serves as an effective medium for conveying moral messages and human values in a profound and persuasive manner.